13.0k views
3 votes
If 2x +9= 23, then 3x =

User Ashfaque
by
5.6k points

2 Answers

5 votes

Answer:

to solve typical question like this first u have to find (x)


2x + 9 = 23 \\ x = (23 - 9)/(2 ) \\ x = (14)/(2) = 7

therefore x = 7

then substitute the answer u got for (x) to the 3(x)

3x

3×7 = 21

User Javi Stolz
by
5.8k points
6 votes

Answer:

21

Explanation:

First you have to solve for x in the equation 2x + 9 = 23. Cancel 9 on both sides. You cancel 9 by subtracting 9 on the left side and on the right side:

23 - 9 = 14.

Now, you have 2x = 14. To isolate the variable, divide by 2 to cancel out 2.

14 / 2 = 7.

This will give you x = 7. Now that you know what x equals, you can substitute x in 3x. This would make it 3(7), or in other words 3 x 7.

3 x 7 = 21.

This means that 3x would be equal to 21. Hope it helps!

User Dan Selman
by
6.0k points